Effect of the Lattice Curvature of Ti-6Al-4V Titanium Alloy on Their Fatigue Life and Fracture Toughness; Physical Mesomechanics; Vol. 23, iss. 5 - Panin V. E. Viktor Evgenyevich; Ovechkin B. B. Boris Borisovich; Hairullin (Khayrullin) R. R. Rustam Ravilievich; Lider A. M. Andrey Markovich; Bordulev Yu. S. Yuri Sergeevich; Panin A. V. Alexey Viktorovich; Perevalova O. B. Olga Borisovna; Vlasov I. V. Ilya Viktorovich (2020, 2020)
Title screen